Age and date for early arrival of the Acheulian in Europe (Barranc de la Boella, la Canonja, Spain). - Josep Vallverdú; Palmira Saladié; Antonio Rosas; Rosa Huguet; Isabel Cáceres; Marina Mosquera; Antonio Garcia-Tabernero; Almudena Estalrrich; Iván Lozano-Fernández; Antonio Pineda-Alcalá; Ángel Carrancho; Juan José Villalaín; et al. (PLoS ONE, 2014)
The first arrivals of hominin populations into Eurasia during the Early Pleistocene are currently considered to have occurred as short and poorly dated biological dispersions. Questions as to the tempo and mode of these early prehistoric settlements have given rise to debates concerning the taxonomic significance of the lithic assemblages, as trace fossils, and the geographical distribution of the technological traditions found in the Lower Palaeolithic record. Here, we report on the Barranc de la Boella site which has yielded a lithic assemblage dating to ∼1 million years ago that includes large cutting tools (LCT). We argue that distinct technological traditions coexisted in the Iberian archaeological repertoires of the late Early Pleistocene age in a similar way to the earliest sub-Saharan African artefact assemblages. These differences between stone tool assemblages may be attributed to the different chronologies of hominin dispersal events. The archaeological record of Barranc de la Boella completes the geographical distribution of LCT assemblages across southern Eurasia during the EMPT (Early-Middle Pleistocene Transition, circa 942 to 641 kyr). Up to now, chronology of the earliest European LCT assemblages is based on the abundant Palaeolithic record found in terrace river sequences which have been dated to the end of the EMPT and later. However, the findings at Barranc de la Boella suggest that early LCT lithic assemblages appeared in the SW of Europe during earlier hominin dispersal episodes before the definitive colonization of temperate Eurasia took place.